ChemInform Abstract: (+)‐ and (‐)‐Spiroreticulatine, a Pair of Unusual Spiro Bisheterocyclic Quinoline‐imidazole Alkaloids from the South China Sea Sponge Fascaplysinopsis reticulata. Issue 50 (December 2015) - Wang, Qi; Tang, Xuli; Luo, Xiangchao; de Voogd, Nicole J.; Li, Pinglin; Li, Guoqiang
Abstract: The title compounds [cf.